STUDY OF TRADE AND DISTRIBUTION OF BASIC NEEDS IN BANDUNG CITY - Tahir, Rusdin; Sukoco, Iwan; Suryanto, Suryanto; Rivani, Rivani (Universitas Padjadjaran, 2024)
The Bandung City Government (TBCG) strives to maintain price stability and ensure the availability of essential commodities. However, the characteristics of trade and distribution in Bandung remain insufficiently identified, limiting effective policymaking. This study explores these characteristics to support policy formulation for price stability and supply availability. Using a qualitative approach, the research involved surveys of 11 large-scale and 125 small-scale retailers, documentation studies, interviews, observations, and focus group discussions (FGDs). Data analysis included transcription, coding, and characteristic description. The findings highlight that four key products: rice, sugar, flour, and cooking oil, require particular attention for supply stability and price control. Stable prices are achieved through cooperation between producers, traders, consumers, and TBCG, which actively monitors the availability of affordable goods. TBCG also shows a strong commitment to protecting the public and traders from price fluctuations, especially during harvest and off-season periods. This study contributes valuable insights into Bandung’s commodity trade dynamics, offering guidance for policymakers to strengthen regulations that ensure the sustainability of supply chains and price stability. Recommendations include enhancing monitoring systems, improving collaboration among stakeholders, and introducing adaptive regulations to address seasonal fluctuations and safeguard long-term food security.